A method for extracting lithium from aluminum electrolysis waste slag and its application
Through the reaction of electrolytic aluminum waste slag with calcium carbonate and concentrated sulfuric acid, combined with a multi-step separation and concentration process, the problems of high energy consumption and hydrogen fluoride gas in the existing technology are solved, and efficient extraction and low energy consumption production of high-purity lithium carbonate are achieved. Suitable for battery industrial applications.
Patent Information
- Application Number
- CN202310119348.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-15
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-02-15
AI Technical Summary
The existing method of extracting lithium with electrolytic aluminum waste slag has high energy consumption, hydrogen fluoride gas generation, equipment safety hazards, and low purity of lithium carbonate. In the prior art, the calcination energy consumption is high and difficult to remove.
After drying and grinding of electrolytic aluminum waste residue, react with calcium carbonate and concentrated sulfuric acid. Through a multi-step separation, washing and concentration process, sodium carbonate and flocculant are used to extract lithium sulfate solution and synthesis of lithium carbonate, and control reaction conditions and additives. to improve lithium leaching rate and product purity.
It has achieved high-purity battery-grade lithium carbonate production, with a lithium leachate rate of more than 98%, low energy consumption, and almost no hydrogen fluoride waste gas, which is suitable for industrial applications.
Smart Images

Figure BDA0004079492410000071 
Figure BDA0004079492410000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrolytic aluminum waste slag treatment, and specifically relates to a method for extracting lithium from electrolytic aluminum waste slag and application thereof. Background Art
[0002] In the prior art, the treatment methods for extracting lithium from electrolytic aluminum waste slag are mainly divided into wet extraction and dry extraction. In the wet extraction, hydrogen fluoride gas will be produced during the reaction process of strong acid to weak acid, which will have high requirements for equipment and production safety protection. Secondly, the reaction temperature is 200-300°C, and the energy consumption is relatively high; the dry extraction is to mix the electrolytic aluminum waste slag and calcium salt evenly, calcine at high temperature for solid phase reaction, and then use strong alkali (sodium hydroxide, potassium hydroxide) for alkaline leaching, and then cool down to generate potassium aluminum sulfate dodecahydrate, remove aluminum, and finally synthesize lithium carbonate. The disadvantages of this method are high calcination energy consumption, and secondly, it is difficult to remove aluminum completely, and the purity of the obtained lithium carbonate is low.
[0003] Patent document CN105293536A discloses a method for extracting lithium from waste aluminum slag, comprising the following steps: reacting lithium-containing waste aluminum slag with concentrated sulfuric acid at 200-400°C to obtain mixture A; leaching mixture A with water and filtering to obtain filtrate A and residue A; adding sodium carbonate to filtrate A for alkaline hydrolysis at 20-40°C, and then filtering to obtain filtrate B and residue B; adding water to residue B to make slurry and then adding lime for causticization, and then filtering to obtain filtrate C and residue C; passing CO2 into filtrate C in step 4) for carbonization reaction, and then filtering, washing, and drying to obtain. In this scheme, the acid leaching reaction temperature is 200-400°C, and the energy consumption requirement is high; and a large amount of hydrogen fluoride gas is generated during the reaction. Although it is absorbed by water washing, it puts forward higher requirements on the air tightness of the corresponding equipment, and also has safety hazards.
[0004] Patent document CN115216645A discloses a method for extracting lithium from electrolytic aluminum waste slag by mixed salt calcination, which uses electrolytic aluminum waste slag as raw material, potassium and calcium salts as auxiliary materials, and adopts mixed salt calcination method, which adopts calcification roasting, potassium salt re-burning, alkali leaching, solid-liquid separation, freezing impurity removal, and purification process. The content of other metal impurity ions in the leaching solution is low, and lithium salts are easily separated and extracted, and industrial lithium hydroxide and lithium carbonate are extracted and separated, and the extraction rate is more than 95%. This scheme needs to be burned twice, the temperature is 750℃~900℃, the roasting and heat preservation time is 0.5~1.0h, and it consumes a lot of energy. Summary of the invention
[0005] In view of this, the present invention provides a method for extracting lithium from electrolytic aluminum waste slag and application thereof.
[0006] The present invention adopts the following technical solutions:
[0007] A method for extracting lithium from aluminum electrolysis waste slag, specifically comprising the following steps:
[0008] After the electrolytic aluminum waste slag is dried and ground to remove carbon and iron impurities, the electrolytic aluminum waste slag fine powder is obtained;
[0009] Add calcium carbonate and water to the fine powder of electrolytic aluminum waste slag, stir evenly, then add concentrated sulfuric acid to react at 80-100°C, separate, and obtain leaching liquid and leaching slag. Wash the leaching slag with pure water, wherein the amount of pure water added is 2-2.5 times the weight of the wet slag. The washing water is used for the next leaching, and the filter residue is sold as a crude calcium fluoride product;
[0010] Add calcium oxide to the leaching solution, adjust the pH to 10-11, separate after reaction, and obtain a filtrate;
[0011] The filtrate is cooled and crystallized, and the crystals are separated and concentrated to obtain a concentrated solution;
[0012] Add sodium carbonate solid to the concentrated solution for reaction, then add flocculant, stir, let stand, separate, and obtain lithium sulfate solution;
[0013] Adding sodium carbonate solution to lithium sulfate solution to react to obtain crude lithium carbonate and mother liquor, cooling the mother liquor and the filtrate together for crystallization, separating and removing crystals, and concentrating to obtain the concentrated solution;
[0014] The obtained crude lithium carbonate is washed, dried and crushed to obtain battery-grade lithium carbonate crystals.
[0015] Furthermore, the mass fraction of the added concentrated sulfuric acid is 98%, and the reaction time of adding concentrated sulfuric acid is 4-8h.
[0016] Furthermore, the amount of calcium carbonate added is 0.5-0.6 times the amount of fluorine element substance in the electrolytic aluminum waste slag, the amount of concentrated sulfuric acid added is 1.0-1.1 times the amount of calcium carbonate substance, and the amount of water added is 3-7 times the mass of the electrolytic aluminum waste slag fine powder.
[0017] Furthermore, the lithium concentration of the filtrate after concentration is 25-30 g / L.
[0018] Furthermore, the amount of sodium carbonate solid added is 1-3 times the amount of calcium ion substances in the concentrated solution, the flocculant is 0.25wt% anionic polyacrylamide solution, and the amount of flocculant added is 0.5-1.5% of the mass of the concentrated solution.
[0019] Furthermore, the specific conditions for adding the sodium carbonate solution to the reaction are: the concentration of the sodium carbonate solution is 250 g / L, and the reaction temperature is 80-90°C.
[0020] Furthermore, the specific steps of cooling and crystallizing the filtrate are as follows: when the temperature of the filtrate drops to 28°C, 10g of sodium sulfate is added as a seed crystal until the solution temperature drops to 5°C, and the solid-liquid separation is performed.
[0021] Furthermore, the specific conditions for drying and grinding are: temperature 100-150° C., time 1-3 h, and passing through a 150-250 mesh sieve.
[0022] The lithium extracted by the above method of extracting lithium from waste aluminum electrolysis slag is used in the battery industry.
[0023] The method for extracting lithium from waste aluminum electrolysis slag of the present invention involves the following chemical reaction equations:
[0024] CaCO3+H2SO4=CaSO4+H2O+CO2↑
[0025] CaSO4+2NaF=CaF2+Na2SO4
[0026] CaSO4+2LiF=CaF2↓+Li2SO4
[0027] 3CaSO4+2AlF3=3CaF2↓+Al2(SO4)3
[0028] CaO+H2O=Ca(OH)2
[0029] Al 3+ +3OH - =Al(OH)3↓
[0030] Fe 3+ +3OH - =Fe(OH)3↓
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] (1) The product prepared by the present invention has high purity and meets the industry standard of battery-grade lithium carbonate, and the lithium leaching rate is ≥98%, which fully utilizes the lithium in the electrolytic aluminum waste slag and recovers resources to the greatest extent;
[0033] (2) The leaching temperature of the present invention is 80-100°C, the conditions are mild, and almost no hydrogen fluoride waste gas is generated, the equipment requirements are low, and the energy consumption is low;
[0034] (3) The present invention achieves a lithium concentration of 25-30 g / L in the lithium sulfate solution by pre-salting, while the conventional process can only achieve 10 g / L. In addition, the higher the lithium concentration in the lithium sulfate solution, the greater the lithium yield during synthesis, the less the mother liquor treatment volume, and the lower the cost. DETAILED DESCRIPTION
[0035] The present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can understand the present invention more clearly.
[0036] Main raw material sources:
[0037] The electrolytic aluminum waste slag comes from Yichang Changjiang Aluminum Industry.
[0038] The main ingredients are shown in Table 1:
[0039] Table 1 Composition of electrolytic aluminum waste slag
[0040] element F Al Na Ca Li other Wt% 53.92 13.13 23.24 2.13 2.39 5.19
[0041] Other raw materials not specifically described in the present invention are already available in the prior art and can be directly purchased from the market.
[0042] Example 1
[0043] This embodiment provides a method for extracting lithium from aluminum electrolysis waste slag, and the specific steps are as follows:
[0044] S1 Drying and crushing: The electrolytic aluminum waste slag is placed in an oven and dried at 120°C for 2 hours. After cooling, it is ground with a ball mill and passed through a 200-mesh sieve. Carbon powder and magnetic impurities are removed by air separation and magnetic separation to obtain fine powder of the electrolytic aluminum waste slag.
[0045] S2 leaching: 500g of electrolytic aluminum waste slag fine powder and 788.3g of calcium carbonate powder were mixed evenly, 3006.44g of pure water was added, and stirred for 15min. Then 858.46g of concentrated sulfuric acid (98%) was added, and solid-liquid separation was performed after stirring at 90°C for 4h to obtain 3776.4g of leaching solution and 1033.44g of filter residue wet weight. At this time, the solid-liquid ratio of the leaching reaction was m (electrolytic aluminum waste slag fine powder + calcium carbonate): m (pure water + sulfuric acid) = 1:3, the amount of calcium carbonate added was 0.55 times the amount of fluorine element in the electrolytic aluminum waste slag, and the amount of sulfuric acid added was 1.1 times the amount of calcium carbonate added;
[0046] Add 2066.88g of pure water to the filter residue, stir evenly and continue stirring for 30 minutes, separate the solid and liquid, and use the washing water for the next leaching. The mass of the filter residue after drying is 567.88g; the amount of pure water added is twice the wet weight of the filter residue.
[0047] The detection method of lithium leaching rate is as follows: the dried filter residue is mixed evenly, 1g of the filter residue is taken, 20mL of aqua regia is added, and then an appropriate amount of pure water is added, and the mixture is heated on an electric furnace until boiling, and the volume is about 10mL, and then the mixture is removed and cooled to room temperature, and the solution is transferred to a 100mL volumetric flask with a funnel. After constant volume, the lithium content is measured to be 3.83ppm. According to the lithium balance, the lithium leaching rate is 98.18%.
[0048] S3 aluminum removal: add calcium oxide solid to the leachate, adjust the solution pH to 11, stir for 40 minutes and separate the solid and liquid to obtain 2577.16g of filtrate, at which the lithium concentration in the filtrate is 3.73g / L and the sodium sulfate content is 20.90%.
[0049] S4 cooling crystallization: cool the filtrate, when the temperature drops to 28 ° C, add 10g of sodium sulfate as a seed crystal, until the solution temperature drops to 5 ° C, solid-liquid separation, separate the sodium sulfate crystals in the solution, and obtain 1569.4g of remaining filtrate. At this time, the Li concentration in the remaining filtrate is 5.94g / L, and the sodium sulfate concentration is 5.89%.
[0050] S5 concentration: The remaining filtrate is heated and evaporated to concentrate the solution to a volume of 300 mL to obtain a concentrated solution, at which the lithium concentration in the concentrated solution is 28.2 g / L.
[0051] S6 Calcium removal: Add 2.06g sodium carbonate solid to the concentrated solution, stir for 30min, then add 3.6g (0.25wt%) anionic polyacrylamide solution, stir for 30min and let stand for 3h, separate the solid and liquid to obtain pure lithium sulfate solution. At this time, the amount of sodium carbonate added is twice the amount of calcium ion substance in the solution, and the amount of flocculant added is 1% of the solution mass.
[0052] S7 lithium carbonate synthesis: pure lithium sulfate solution and 250g / L sodium carbonate solution are synthesized into lithium carbonate at 85°C to obtain crude lithium carbonate and mother liquor. At this time, the lithium content in the mother liquor is 2.43g / L. The mother liquor is returned to step S4 for cooling and crystallization, sodium sulfate decahydrate is separated, and the remaining liquid enters the next step in sequence;
[0053] S8 washing, drying, crushing and packaging: the crude lithium carbonate product obtained in S7 is washed, dried, crushed and packaged to obtain 81.56 g of battery-grade lithium carbonate.
[0054] Example 2
[0055] This embodiment provides a method for extracting lithium from electrolytic aluminum waste slag, and its raw materials and steps are basically the same as those in Example 1, except that the amount of calcium carbonate added is 1.2 times the amount of fluorine element in the electrolytic aluminum waste slag.
[0056] Finally, 81.61 g of battery-grade lithium carbonate was obtained, and the lithium leaching rate was 98.22%.
[0057] Example 3
[0058] This embodiment provides a method for extracting lithium from electrolytic aluminum waste slag, and its raw materials and steps are basically the same as those in Example 1, except that the amount of sulfuric acid added is 1.2 times the amount of calcium carbonate added.
[0059] Finally, 81.65% battery-grade lithium carbonate was obtained, and the lithium leaching rate was 98.27%.
[0060] Comparative Example 1
[0061] This invention provides a method for extracting lithium from waste aluminum electrolysis residues. The waste aluminum electrolysis residues used are the same as those in Example 1. The steps are described in Example 1 of a method for preparing a lithium salt or positive electrode material for a lithium ion battery disclosed in Patent Document 115286020A. The specific steps are as follows:
[0062] S1 Crushing: Take the electrolytic aluminum waste slag and dry grind it to 100 mesh to obtain the electrolytic aluminum waste slag fine powder.
[0063] S2 leaching: Take 200g of fine powder of electrolytic aluminum waste slag, add 6L of soluble calcium salt solution, in which the concentration of calcium chloride is 5.3wt%, stir for 15min, add 380g of calcium oxide solid, react at 80℃ for 4h, and then separate the solid and liquid to obtain the leaching solution and leaching slag.
[0064] S3 washing and drying: washing the leached residue with pure water until the pH is less than 8, and then drying the leached residue to obtain dried leached residue solid.
[0065] The dry leached residue obtained in Comparative Example 1 was used to measure the lithium content in the residue using the lithium leaching rate detection method in Example 1. After lithium balance, the lithium leaching rate was found to be 56.57%.
[0066] Comparative Example 2
[0067] This comparative example provides a method for extracting lithium from waste aluminum electrolysis slag, and its raw materials and steps are basically the same as those of comparative example 1, except that the reaction temperature in step S2 is changed from 80°C to 95°C.
[0068] Similarly, the leached solid slag was subjected to the lithium leaching rate detection method in Example 1, and after lithium balance, the lithium leaching rate was found to be 67.1%.
[0069] The products prepared in Examples 1-3 were measured according to the battery-grade lithium carbonate industry standard YS / T582-2013. The results are shown in Table 2.
[0070] Table 2 Performance indicators of products prepared in Examples 1-3
[0071]
[0072]
[0073] It can be seen from Table 2 that the products obtained in Examples 1-3 all meet the battery-grade lithium carbonate industry standard YS / T582-2013, the product purity is high, the lithium leaching rate is high, the leaching conditions are mild, the temperature is low, and no hydrogen fluoride waste gas is generated during the preparation process, which is conducive to widespread promotion and suitable for industrial production.
[0074] It can be seen from the lithium leaching rates of Examples 1-3 that the lithium leaching rate does not change much with the increase in the amount of calcium carbonate and sulfuric acid added. Therefore, it is best to control the addition amount within the above-given range. This process not only has a high lithium leaching rate, but also the finished lithium carbonate meets the battery-grade lithium carbonate standard.
[0075] By comparing the lithium leaching rates of the embodiments and the comparative examples, it can be seen that the lithium leaching rate of the alkaline leaching in the comparative example is not high, and the lithium concentration in the solution is low, and the concentration requires more energy. Since the sodium chloride content in the solution is relatively high, the lithium concentration of the solution can only be increased to about 10-13g during the concentration process. In addition, it can be seen from Comparative Examples 1-2 that increasing the leaching temperature, although the leaching rate is improved, is still far behind the lithium leaching rate in the method of the present application.
[0076] The above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for extracting lithium from electrolytic aluminum waste slag, characterized in that: The specific steps include: The electrolytic aluminum waste slag is dried and ground to remove carbon and iron to obtain electrolytic aluminum waste slag fine powder; Add calcium carbonate and water to the fine powder of electrolytic aluminum waste slag, stir evenly, then add concentrated sulfuric acid to react at 90°C, separate, and obtain leaching solution and leaching slag; Add calcium oxide to the leaching solution, adjust the pH to 10-11, separate after reaction, and obtain a filtrate; The filtrate is cooled and crystallized, and the crystals are separated and concentrated to obtain a concentrated solution; Add sodium carbonate solid to the concentrated solution for reaction, then add flocculant, stir, let stand, separate, and obtain lithium sulfate solution; Adding sodium carbonate solution to the lithium sulfate solution, reacting and separating to obtain crude lithium carbonate and mother liquor, cooling the mother liquor and the filtrate together for crystallization, separating and removing the crystals, and concentrating to obtain the concentrated solution; The obtained crude lithium carbonate is washed, dried and crushed to obtain battery-grade lithium carbonate crystals; The mass fraction of the added concentrated sulfuric acid is 98%, and the reaction time of adding concentrated sulfuric acid is 4h; The amount of calcium carbonate added is 0.5-0.6 times the amount of fluorine in the electrolytic aluminum waste slag, the amount of concentrated sulfuric acid added is 1.0-1.1 times the mass of calcium carbonate, and the amount of water added is 3-7 times the mass of the electrolytic aluminum waste slag fine powder.
2. The method for extracting lithium from electrolytic aluminum waste slag according to claim 1, characterized in that: The lithium concentration of the filtrate after concentration is 25-30 g / L.
3. The method for extracting lithium from electrolytic aluminum waste slag according to claim 1, characterized in that: The amount of sodium carbonate solid added is 1-3 times the amount of calcium ion substances in the concentrated solution, the flocculant is 0.25wt% anionic polyacrylamide solution, and the amount of flocculant added is 0.5-1.5% of the mass of the concentrated solution.
4. The method for extracting lithium from electrolytic aluminum waste slag according to claim 1, characterized in that: The specific conditions for adding the sodium carbonate solution to the reaction are: the concentration of the sodium carbonate solution is 250 g / L, and the reaction temperature is 80-90°C.
5. The method for extracting lithium from electrolytic aluminum waste slag according to claim 1, characterized in that: The specific steps of cooling and crystallizing the filtrate are as follows: when the temperature of the filtrate drops to 28° C., 10 g of sodium sulfate is added as a seed crystal until the solution temperature drops to 5° C., and the solid and liquid are separated.
6. The method for extracting lithium from electrolytic aluminum waste slag according to claim 1, characterized in that: The specific conditions for drying and grinding are: temperature 100-150°C, time 1-3h, and passing through a 150-250 mesh sieve.
7. Application of lithium extracted by the method for extracting lithium from waste aluminum electrolysis slag as described in any one of claims 1 to 6 in the battery industry.
